A preliminary survey of water physico-chemical characteristics and aquatic macroinvertebrate communities in El Mekhada marsh, north-eastern Algeria. Issue 2 (3rd April 2018) - Saoudi, Messaoud; Tadjine, Aicha; Guerfi, Sarra; Necer, Abdeldjabar
Abstract: The water physico-chemistry and aquatic macroinvertebrates were investigated for the first time in El Mekhada marsh, Algeria. The aim of this study was to assess the general ecological condition of the marsh by studying the spatial and seasonal variation of physico-chemical parameters and macroinvertebrate communities. Sampling was conducted at four sites surrounding the marsh, in wet and dry seasons from February to September 2016. Physico-chemical characteristics were similar among sampling sites and seasons ( p  > 0.05), except for water temperature, which showed significantly higher values in the wet period than in the dry period ( p  < 0.05). A total of 1066 macroinvertebrate individuals belonging to 43 taxa were collected. Macroinvertebrate descriptors revealed no significant variation across the marsh ( p  > 0.05), and only taxa abundance was significantly higher in the wet season than in the dry season ( p  < 0.05). NMDS reflected the previously detected variation and showed a clear separation in macroinvertebrate assemblages between seasons. The SIMPER analysis revealed that the mean abundance of most taxa was lower in the dry season. This study highlights that the studied marsh is taxonomically rich (34 families); therefore, its conservation and protection is necessary.